2013
DOI: 10.3402/tellusb.v65i0.20554
|View full text |Cite
|
Sign up to set email alerts
|

Statistical adjoint sensitivity distributions of meteorological forecast errors of Asian dust transport events in Korea

Abstract: A B S T R A C TThe sensitivities of meteorological forecast errors associated with Asian dust transport events to changes in the initial state were evaluated for 46 occurrences that affected the Korean Peninsula from 2005 to 2010. Adjoint-based sensitivities were used to determine these sensitivities. Sensitive regions were located primarily over two regions upstream from the Korean Peninsula: the northern source region, including areas of Mongolia and northern China, and the Tibetan Plateau. Depending on tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Asian dust events are an important spring phenomenon in East Asia. Recently, the importance of predicting Asian dust events on the Korean Peninsula has been increased because of the increasing number of events (Sugimoto et al 2003), the increasing occurrence frequency in fall and winter in South Korea (Kim et al 2013), and the longer duration of individual events. To mitigate the social and economic damage from Asian dust events, accurate forecasts of such events are essential.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Asian dust events are an important spring phenomenon in East Asia. Recently, the importance of predicting Asian dust events on the Korean Peninsula has been increased because of the increasing number of events (Sugimoto et al 2003), the increasing occurrence frequency in fall and winter in South Korea (Kim et al 2013), and the longer duration of individual events. To mitigate the social and economic damage from Asian dust events, accurate forecasts of such events are essential.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the effect of meteorological forecasts on chemical transports, Sistla et al (1996), Biswas and Rao (2001), Zhang et al (2007), and Liu et al (2011) showed that small uncertainties in meteorological input to transport models result in large uncertainties in ozone and CO 2 predictions. In this sense, the uncertainties in the meteorological forecasts could cause large errors in Asian dust forecasts on the Korean Peninsula Kim and Kay 2010;Kim et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations